Conceptual Metaphors for Designing Smart Environments: Device, Robot, and Friend - Kim, Jingoog; Maher, Mary Lou (Frontiers in Psychology, 2020)
Metaphor is a design tool that can support designers in forming and exploring new design concepts during the process of designing. Digital technologies embedded in built environments provide an opportunity for environments to be more intelligent and interactive. However, most architectural concepts associated with smart environments such as smart homes and intelligent buildings tend to focus on how advances in technology can improve the quality of the residential environment using automation and not on how people interact with the environment. We posit that conceptual metaphors of device, robot, and friend, can open up new design spaces for the interaction design of smart environments. We present three metaphorical concepts that can frame new ways of designing smart environment that focuses on interaction rather than building automation, each of which have distinct HCI techniques.